2002
DOI: 10.1002/art.10542
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to high‐density lipoprotein and β2‐glycoprotein I are inversely correlated with paraoxonase activity in systemic lupus erythematosus and primary antiphospholipid syndrome

Abstract: Objective. To determine the prevalence of antihigh-density lipoprotein (anti-HDL) antibodies and to establish a possible relationship between anti-HDL, anticardiolipin antibodies (aCL), anti-␤ 2 -glycoprotein I (anti-␤ 2 GPI), and paraoxonase (PON) activity in patients with systemic lupus erythematosus (SLE) and primary antiphospholipid syndrome (APS).Methods. Thirty-two patients with SLE and 36 with primary APS were enrolled in a cross-sectional study. Twenty age-and sex-matched healthy subjects were used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
129
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(146 citation statements)
references
References 103 publications
13
129
2
1
Order By: Relevance
“…However, on the basis on multiple regression model only aβ2-GPI IgG were found an independent predictor of decreased paraoxonase activity (r= -0.483, p = 0.003). The reported interactions may be relevant to the development of atherosclerosis in SLE and PAPS (Delgado Alves et al, 2002). Other observations also supported findings on the role of paraoxonase activity in SLE-related vascular abnormalities.…”
Section: Selected Pathomechanisms In Atherogenesis -The Role Of Antipsupporting
confidence: 81%
See 1 more Smart Citation
“…However, on the basis on multiple regression model only aβ2-GPI IgG were found an independent predictor of decreased paraoxonase activity (r= -0.483, p = 0.003). The reported interactions may be relevant to the development of atherosclerosis in SLE and PAPS (Delgado Alves et al, 2002). Other observations also supported findings on the role of paraoxonase activity in SLE-related vascular abnormalities.…”
Section: Selected Pathomechanisms In Atherogenesis -The Role Of Antipsupporting
confidence: 81%
“…However, study performed in subjects with idiopathic aPL showed association between aCL IgG titre and CIMT. In addition, it confirmed aCL IgG as well as homocysteine and fibrinogen as independent predictors of CIMT indicating that measurement of homocysteine and fibrinogen may help to identify aPL patients who are more likely to develop atherosclerosis (Ames et al, 2002). More recent studies also confirmed a usefulness of CIMT measurement in a detection of early atherosclerotic changes and showed an association between CIMT and aPL in thrombotic PAPS patients (Ames et al, 2009a) as well as in patients with APS secondary to SLE (Belizna et al, 2008).…”
Section: Atherosclerosis In Primary Antiphospholipid Syndromementioning
confidence: 76%
“…Indeed, the microbiota of inflammatory bowel disease (IBD) patients has a low abundance of Faecalibacterium prausnitzii, a member of this phylum with a known and well characterized anti-inflammatory effect (34)(35)(36)(37). In spite of the fact that the absence of differences in total antioxidant capacity between SLE and controls is in agreement with previous studies in SLE subjects (38,39), there is no consensus about it in the literature. While some authors have reported lower levels in autoimmune diseases (40,41), others have found higher ones (42).…”
Section: Discusionmentioning
confidence: 81%
“…The latter study also showed that the elevated PL titre was negatively related to the antioxidant capacity of PON [17]. PON accounts for most of the antioxidant of properties of HDL against LDL oxidation [18] and its activity is known to be decreased in PAPS [19].…”
Section: Discussionmentioning
confidence: 99%